Taxonomic Characteristics of Twelve New Yeast Species Isolated in 2023 Not Listed in the National Species List of Korea - Jung-Woo Ko; Ye-Jin Kim; Eun-Jeong Kim; Sang-Su Lee; Seong-Min Choi; Chorong Ahn; ChangMu Kim; Cheon-Seok Park (한국균학회지)
With a history spanning 9,000 years, yeast has played a central role in the traditional production of fermented foods, particularly alcohol and bakery. Recent research has highlighted the versatility of yeast in various industries, including the production of bioactive compounds, bioethanol, pigments, and enzymes, and as a host for molecular biology studies. In Korea, yeast isolation has traditionally focused on traditional fermented foods such as soybean paste. However, there is a growing trend in the isolation and characterization of yeasts from natural environments such as flowers and fruits for industrial applications. In this study, we isolated and identified 12 yeasts from various natural environments in Korea, including botanical gardens and parks that are not listed on the National Species List of Korea (NSLK). These newly discovered species included Sakaguchia oryzae, Cystobasidium raffinophilum, Meira argovae, Kazachstania humilis, Meyerozyma smithsonii, Anthracocystis trispicatae, Naganishia brisbanensis, Tremella yokohamensis, Kwoniella shandongensis, Kwoniella newhampshirensis, Aureobasidium proteae, and Rhodotorula dairenensis.